Implications of facilitation and heterogeneity for plant community restoration in the Rocky Mountain region - Harris, Rebecca F., author; Paschke, Mark, advisor; Havrilla, Caroline, committee member; Rhoades, Chuck, committee member; Smith, Melinda, committee member (Colorado State University. Libraries, 2023)
Seeding is the most widespread and viable method to revegetate degraded dryland ecosystems. Despite its prevalence, efforts to establish plants through seeding frequently fail. Variable weather conditions, competition with dominant and invasive species and herbivory pose barriers to the establishment of seeded plants. As a result, there is a great need and demand for innovative restoration practices that can aid revegetation efforts. Pit, mound and slash pile treatments create spatial and resource heterogeneity and thus can provide niches for different plants to find suitable habitat. I completed a four-year study that tested the impacts of seeding in conjunction with heterogeneity treatments on measures of plant community structure and cover compared to untreated but seeded plots and unseeded controls. Research sites were located in California Park, Colorado USA, a 11,000-ha Artemisia cana (silver sagebrush) meadow in the Medicine Bow Routt National Forest. In 2018, replicated test plots containing four treatments (unseeded control, seeded only, seeded plus soil pits and mounds, and seeded plus slash) were established at degraded sites in California Park. Seeded plots received a high diversity native seed mix (39 species) at a high rate (1496 Pure Live Seed [PLS] / m2). I monitored seeded species density and total plant species cover in the summers of 2019 through 2022. I analyzed treatment effects on plant Shannon Wiener diversity (H), richness, seeded abundance (plants / m2), Pielou's evenness (J) and percent cover with linear mixed-effects models. Plots that received the seeded only and seeded plus soil pits and mounds treatments contained higher seeded species diversity than control plots in 2019 and 2022. While seeded plus slash pile treatment plots increased seeded species diversity in the first year of monitoring, this effect diminished after 2019. It is important to note, no seeded diversity differences emerged between heterogeneity treatment plots and untreated but seeded plots in any year. Findings suggest that seed application can increase the diversity of desirable seeded species and may be a useful tool to shift plant community composition. Shrub subcanopies accumulate moisture and nutrients in a manner that can facilitate understory plants. Consequently, seeding beneath shrubs may improve seedling establishment and survival in dryland ecosystems where harsh environmental conditions are present. I set up a study to evaluate whether seeded shrub islands had higher seeded species abundance and richness compared to seeded interspaces and unseeded controls. Study sites were located outside of Grand Junction, Colorado in Dominguez Escalante and McInnis Canyons National Conservation Areas (NCA) (Figure 2.1). Six sites were established in fall of 2020, three within sagebrush and three within salt desert shrublands. Five seeded shrub islands, five seeded interspaces, five unseeded shrub island controls and five unseeded interspace controls were established at each site. In addition, I evaluated if the impacts of these treatments were different between sagebrush and salt desert shrublands. Furthermore, I assessed whether plant functional groups and soil chemical properties were impacted by treatment type. I analyzed treatment effects on seeded species richness, seeded species abundance, cover by plant functional group, surface soil moisture, temperature and chemical properties with separate linear mixed-effects models. While sub canopy microsites were on average nutrient enriched and cooler than interspace plots, they did not facilitate seeded species establishment. In contrast to expectations, seeded interspaces contained higher seeded species richness than all other plot types. Lower richness in seeded shrub islands may be due to sodic, saline and or saline-sodic soil conditions found beneath shrubs within the salt desert. In addition, high cover of introduced perennial grasses beneath shrub islands may prevent seedling establishment at sagebrush sites. Results suggest that interspaces provide more favorable conditions for seeded plant establishment than shrub islands in both systems. Land managers are interested in levering positive plant-plant interactions (i.e., facilitation) and heterogeneity to improve seeded plant establishment and plant community restoration outcomes. I investigated whether applying a native seed mix either beneath shrub islands, or in tandem with heterogeneity treatments, increased seeded plant establishment and diversity respectively. I hope this research can contribute to improving plant community restoration outcomes in degraded dryland ecosystems.
Keywords: facilitation; plant community ecology; seedling establishment; heterogeneity; dryland; restoration